A novel LSB-based RDH with dual embedding for encrypted images. (10th April 2019) - Mondal, Jayanta; Swain, Debabala; Panda, Devee Darshani
A novel reversible data hiding technique for encrypted images is proposed in this paper. Encryption helps achieving privacy which is a necessity for sensitive imagery such as medical and military images. In encrypted domain data embedding capacity remains a big challenge. A dual embedding scheme is proposed to enhance the additional data hiding capability. The general architecture includes a content owner, a data hider, and a receiver. This scheme is subjected to work on 512 × 512 grey-scale image. The encryption is done using a random 512 × 512 key matrix followed by a two phase data hiding technique to embed bits differently in odd and even blocks. Experiments are conducted in different block sizes in the embedding phase to achieve maximum data hiding potential. Experimental results show a huge increase in embedding capability. The error rate has significantly reduced over 50% in the recovered image and visual quality and image recovery is better than the existing methods.